Flawed foundation is the root cause of failure of medicine and precludes cures for chronic diseases - Jianqing Wu; Ping Zha (Global Journal of Cancer Therapy - Peertechz Publications, 2023)
Modern (science-based) medicine adopted four presumptions when it evolved from ancient experienced-based mind-body medicine. To understand its failure in finding cures for chronic diseases, we examined four presumptions and found that statistical population of health properties does not exist for most research purposes, mathematical models are misused to model intensive properties, synthetic drugs are inherently more dangerous than nature-made medicines under their respective application conditions, and reductionist treatments are inferior and inherently dangerous. We found that clinical trials are valid only for research where the treatment effect is much stronger than the total effects of all interfering or co-causal factors or errors introduced by misused mathematical models can be tolerated. In all other situations, clinical trials introduce excessive errors and fail to detect treatment effects or produce biased, incorrect, or wrong results. We further found that chronic diseases are the manifestation of small departures in multiple processes attributes in distinctive personal biological pathways networks, that modern medicine lacks the required accuracy for accurately characterizing chronic diseases, and that reductionist treatments are good at controlling symptoms and safe for short-term uses. For all stated reasons, as long as modern medicine continues relying on flawed presumptions, it can never find predictable cures for chronic diseases. By implication, predictable cures to chronic diseases are adjustments to lifestyle, dietary, emotional, and environmental factors to slowly correct departures in process attributes responsible for chronic diseases.